STATE AS STARTUP: CONNECTING THE UNCONNECTED IN ANDHRA PRADESH - Prasad, Revati (AoIR Selected Papers of Internet Research, 2020)
This paper examines the Andhra Pradesh State Fiber Net Ltd (APSFL) or APFiber, a state corporation established to “connect the unconnected” in the south Indian state of Andhra Pradesh. APSFL built a network of 24,000 kilometers of aerial fiber that delivered internet, cable and voice services to roughly 650,000 rural subscribers by early 2019. Through interviews with APSFL staff and the local cable operators that are the last-mile workers of the network, I examine the particularities of the connectivity on offer, one that pairs internet with cable TV and places the state government within citizens’ homes and on their TV screens. I unearth the rationales employed in support of this effort, that it would serve growth, glory and governance. Paying attention to the technical and social arrangements that comprised the service, I analyze how these goals translated into practice. I argue that the connectivity on offer serves capital and consolidates state power, where surveillance becomes both routine and revenue. In the name of the development imperative enabled by a tech subnationalism, APFiber furthers the penetration of both state and capital in the lives of those they deem unconnected. I see the founding of a regime of extraction and control. The state valorizes the culture of Silicon Valley, adopts its logics and practices, and comes to see itself as a startup.